Técnicas pictóricas : el aerógrafo - Chaves, José Mario; Moreira Schenone, Edgardo (San José, C.R. : Universidad de Costa Rica, Vicerrectoría de Acción Social, 1990)
Presenta una descripción del uso y las técnicas del aerógrafo
Keywords: AEROGRAFIA